Implementasi Firman Tuhan dalam Mewujudkan Pendidikan Pluralisme Bagi Sekolah Minggu: Sebuah Kajian Pendidikan Agama Kristen - Elista Simanjuntak (UKI Press, 2023)
This research is motivated by the conflict over the demolition and burning of a church at the Indonesian Christian Huria Suka Makmur in Aceh Singkil. The main purpose of this research is to provide education that Sunday School is a Christian educational institution that teaches and trains children to experience the true growth of faith in Jesus and teaches them how to be open and accept any differences that exist, in terms of religion, ethnicity, race, and so on. The method used in this study is descriptive qualitative by describing the Bible and its implementation in realizing pluralism education for Sunday Schools. The results of the study show that the Bible as the essence of forming the character of pluralism in children from an early age in the midst of diversity can be applied through the educational realm of Sunday School institutions on the basis that the Bible is the fundamentalism of diversity. In addition, the Bible is also a source of teaching legitimacy and the nature of pluralism education in Sunday Schools.